2020
DOI: 10.2196/18420
|View full text |Cite
|
Sign up to set email alerts
|

A Remotely Delivered, Peer-Led Physical Activity Intervention for Younger Breast Cancer Survivors (Pink Body Spirit): Protocol for a Feasibility Study and Mixed Methods Process Evaluation

Abstract: Background Younger breast cancer survivors consistently report a greater impact of their cancer experience on quality of life compared with older survivors, including higher rates of body image disturbances, sexual dysfunction, and fatigue. One potential strategy to improve quality of life is through physical activity, but this has been understudied in younger breast cancer survivors, who often decrease their activity during and after cancer t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 66 publications
(68 reference statements)
0
26
0
Order By: Relevance
“…Data were collected from October 2019 – July 2020. Protocol details were previously published (Weiner et al, 2020 ). Briefly, recruitment was led by Haus of Volta and focused on social media postings (Facebook and Instagram) in groups tailored to younger breast cancer survivors, including the Young Survival Coalition and Living Beyond Breast Cancer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were collected from October 2019 – July 2020. Protocol details were previously published (Weiner et al, 2020 ). Briefly, recruitment was led by Haus of Volta and focused on social media postings (Facebook and Instagram) in groups tailored to younger breast cancer survivors, including the Young Survival Coalition and Living Beyond Breast Cancer.…”
Section: Methodsmentioning
confidence: 99%
“…For a comprehensive intervention description, see Weiner et al(Weiner et al, 2020 ). The Pink Body Spirit program was based on an effective exercise intervention for older survivors that was delivered in-person and via phone by a professional interventionist in a clinical research study (Hartman et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The device contains a triaxial accelerometer, optical heart rate monitor, altimeter, and vibration motor. The Fitbit uses a proprietary algorithm to determine activity levels, which are defined as vigorous, moderate, light, or sedentary [ 20 ]. Studies have shown that the Fitbit has an accuracy rating of 85.4% in distinguishing activity levels, specifically in distinguishing sedentary and light activity from moderate-to-vigorous activity [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…16,17 These technology-based interventions could allow easy 24-hour access without time or cost constraints. 18 In recent years, numerous studies have used such programs 16,[19][20][21][22][23][24] and have shown the effectiveness of the programs in providing information and coaching or supporting to socially excluded groups including racial/ethnic minorities. 23,25 The retention of participants in technology-based intervention studies was reported to be far more complicated and challenging compared with conventional studies targeting racial/ ethnic minorities because of the limited number of individuals with access to the internet where these interactions occur.…”
mentioning
confidence: 99%